2015
DOI: 10.3945/ajcn.114.089664
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine requirements of enterally fed term and preterm neonates

Abstract: Background: Phenylalanine, which is an essential aromatic amino acid, is either used for protein synthesis or irreversibly hydroxylated to tyrosine. The provision of optimal amounts of dietary phenylalanine is not only important for growth and development but might also influence catecholamine synthesis and release rates. The current recommended aromatic amino acid requirement for infants aged 0-6 mo is based on the amino acid content of human milk. Objective: We quantified the requirements for phenylalanine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…One determined phenylalanine requirements in the presence of excess tyrosine in adult males to be 9.1 mg • kg −1 • d −1 (14). The other determined the minimum phenylalanine requirements in enterally fed term and preterm neonates to be 58 mg • kg −1 • d −1 and 80 mg • kg −1 • d −1 , respectively (38). It will be beneficial to determine TAA requirements in healthy human pregnancy, which will help update the DRI recommendations, and to set recommendations in women with mPKU, because tyrosine is an indispensable amino acid in this population.…”
Section: Discussionmentioning
confidence: 99%
“…One determined phenylalanine requirements in the presence of excess tyrosine in adult males to be 9.1 mg • kg −1 • d −1 (14). The other determined the minimum phenylalanine requirements in enterally fed term and preterm neonates to be 58 mg • kg −1 • d −1 and 80 mg • kg −1 • d −1 , respectively (38). It will be beneficial to determine TAA requirements in healthy human pregnancy, which will help update the DRI recommendations, and to set recommendations in women with mPKU, because tyrosine is an indispensable amino acid in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Animal-based food production generally has a bigger climate impact than plant-based From the introduction of the first infant formula onwards, milk protein and its processes have been optimized to provide the most optimal amino acid profiles in infant formula. However, based on requirement studies [45][46][47][48][49][50], there is still no intact protein to provide the right composition of essential amino acids. Therefore, the addition of free amino acids is unavoidable, which has its disadvantages.…”
Section: Plant Protein-based Infant Formulamentioning
confidence: 99%
“…To date, the amino acids provided by infant formula have been roughly based on the average amino acid content in human milk (15). In a series of studies, we used the indirect amino acid oxidation (IAAO) technique to assess infant amino acid requirements and showed that infant formulas are likely to provide an excess and unbalanced amount of essential amino acids (16)(17)(18)(19)(20)(21). Based on these outcomes, a modified infant formula was developed with an optimized amino acid composition that facilitated a protein content reduction of 20%.…”
Section: Introductionmentioning
confidence: 99%